Depression and anxiety symptoms in adolescents and young adults in Greece: Prevalence and associated factors - Maria Basta; Katerina Micheli; Katerina Koutra; Maria Fountoulaki; Vasilis Dafermos; Maria Drakaki; Konstantinos Faloutsos; Eugenia Soumaki; Dimitrios Anagnostopoulos; Nikolaos Papadakis; Alexandros N. Vgontzas (Journal of Affective Disorders Reports, 2022)
Background: Few studies have investigated depression-anxiety in adolescents/young adults in Greece. We examined the prevalence of depression/anxiety and its correlates in a large, representative, population-based sample of young Greeks. Methods: A structured telephone questionnaire was conducted in 2771 adolescents/young adults aged between 15 and 24 years (mean age: 20.47 ± 2.83 years). Depression/anxiety symptoms were assessed using the PHQ-9 and GAD-7 scales, respectively. Sociodemographics, mental health, and psychological parameters were also examined. Moderate to severe depression and anxiety symptoms were defined with PHQ-9≥10 and GAD-7≥10, respectively. Analysis was conducted using multivariable linear and logistic regression models. Results: In our sample, 803 (29%) and 416 (15%) participants reported depressive and anxiety symptoms, respectively. In multivariable analysis, depression was associated with female sex, younger age, mental health history, substance use, dyslexia, lower quality of life and social seclusion (all p < 0.05). Within youth with mental health history, depression was associated with younger age, female sex, dyslexia, attention difficulties, and substance use (p < 0.05). Multivariable analysis revealed similar to depression associations between anxiety and sociodemographic and clinical correlates. Mental health history plus attention/learning problems and substance use was associated with a 57% chance of being depressed. Neither depression nor anxiety was associated with unemployment/low income. Limitations: Due to cross-sectional design, causality between correlated factors cannot be examined. Conclusions: Depression and anxiety symptoms among youth in Greece are frequent and associated more with previous mental health history and co-existing attention/ learning difficulties, and substance use, rather than known socioeconomic factors. These results may affect preventive health strategies’ priorities.